Analysis of Deformation of Float Glass with Heat Treatment in Vehicle Windshield Applications - Eko Julianto; Elkana Bilak Lopo; Sunaryo Sunaryo (Automotive Experiences, 2020)
The purpose of this study was to determine the shape change characteristics of float sheet glass using heat treatment experiments on its surface. This involved the use of a float glass type with a thickness of 5 mm, a width of 840 mm, and length of 1350 mm as the test specimen and the heat transfer experiments and treatment were conducted through conduction with the heat distribution recorded to be between 34 °C and 600 °C at every 5 minutes within 60 minutes in a heating furnace. The analysis focused on the characteristics of the glass surface exposed to fire with emphasis placed on the temperature during the deflection changes in the entire glass surface, the dimensional changes at the edges of the glass which follow the glass printing pattern, and the changes in temperature on the upper and lower surfaces of the curved glass mold. The results showed the existence of a very clear change in each temperature or conduction heat when the shape of the glass is changed to curve with the ideal shape observed to have changed at a temperature of 482.50 °C. Moreover, dimensional changes were 1.0427 m2 and the variations in the temperature were 107.55 °C and the continuous increase in the heat was to have led to a faster change in the glass shape by 11.2°. This, therefore, means a higher temperature or room temperature affects the firing rate of glass bending and also increases the rate of heat absorption.